The two faces of social capital in private flood mitigation: opposing effects on risk perception, self-efficacy and coping capacity. Issue 8 (3rd August 2017) - Babcicky, Philipp; Seebauer, Sebastian
Abstract : Impacts of flooding are expected to increase, most notably in residential areas. As a consequence, private households are increasingly encouraged to engage in private flood mitigation complementary to public measures. Despite the growing literature on private flood mitigation, little is known about how social capital influences households' perception of and coping with flood risks. This study draws on survey data of 226 flood-prone households in two Austrian Alpine municipalities, both recently affected by riverine flooding. We show that social capital cuts both ways: on the positive side, social capital increases perceived self-efficacy and provides critical support during and most notably after flood events. On the negative side, social capital reduces flood risk perceptions of private households. While social ties are effective when responding to and recovering from floods, the expectation of social support downplays risk, making precautionary action by households less likely. The results also show that flood-affected households receive more social support than they provide to others. In the long-run, this can lead to a problematic reciprocity imbalance, challenging the long-term stability of the interpersonal exchanges underlying social capital. Among the various sources of social support, informal social networks (neighbours, friends and relatives) provide the most important workforce in the response and recovery phase of a flood event. It is therefore crucial for flood risk management to recognise and promote the protective quality of social capital alongside conventional structural and non-structural measures.